PISA reading literacy assessment and senior high school reading literacy assessments: How do they differ? - Zaim, M; Refnaldi, Refnaldi; Zainil, Yetti; Ramadhani, Fiona (International Journal of Research in Counseling and Education, 2021)
The Program for International Student Assessment (PISA) is an international program assessment to evaluate and determine the education system's effectiveness by focusing on reading, mathematics, and science. This study aims to analyze the differences between PISA reading literacy assessment and senior high school reading literacy assessment in West Sumatera. Reading literacy is abilities and skills in reading needed in everyday life to develop students' knowledge and potential. The method of this study was comparative method. Data were taken from PISA reading literacy 2018, which OECD published, and reading tests made by English teachers from ten Senior High Schools in West Sumatera. In addition, this study used document analysis to collect the data. The differences between PISA reading literacy assessment and reading literacy assessment at senior high school were seen from eight indicators: cognitive process, form of text, types of text, form of test, situation, types of question, level of question, text medium, and text environment. It was found that PISA reading literacy assessment was more complex compared to reading literacy assessment at senior high school.